Poids et plis cutanés chez les Esquimaux de Fort Chimo (Nouveau - Québec) - Auger, Franklin (Anthropologica, 2022)
The Eskimo village of Fort Chimo is located at 58° 7' N, 68° 24' W on the west shore of the Koksoak River, thirty five miles south of Ungava Bay. Traditional cultural and social values have remained relatively unchanged there until fairly recently. However, as a consequence of closer contact with more technically advanced societies, this community is now rapidly undergoing substantial socio-cultural changes. Along with these changes, the people of Fort Chimo have also undergone genetic changes due to intermarriages with Whites and to a lesser extent, with Indians. In the present study age, weight and three skinfolds are analysed. We can show some differences between hybrids and non hybrids.